An experimental investigation on the post-cracking behaviour of Recycled Steel Fibre Reinforced Concrete - Frazão, Cristina Maria Vieira (2018)
Steel fibres resulting from the industry of tyre recycling can be efficiently employed for the reinforcement of concrete structures. Recycled Steel Fibre Reinforced Concrete (RSFRC) is a promising candidate with technical, environmental and economic benefits for the development of ductile, high strength and durable constructive systems, as it is required for breakwater elements used on the protection of coastal zones. For assessing the potentialities of recycled steel fibres (RSF) as concrete reinforcement, an experimental program was performed in the present work by comparing the following properties of concrete reinforced with industrial steel fibres (ISF) and with RSF: compressive strength, modulus of elasticity, flexural strength, flexural toughness and indirect tensile strength. Under chloride attack, the durability performance of RSFRC requires the assessment of its corrosion resistance. To evaluate the corrosion effects on the post-cracking response of RSFRC, double edge wedge splitting tensile tests were conducted in RSFRC specimens previously exposed to aggressive chloride environment. The obtained results demonstrate that, for the adopted industrial and recycled fibres, the last ones had not inferior post-cracking strengthening performance than the first ones. The corrosion action caused a slight decrease of the average post-cracking tensile strength of the RSFRC. The small percentage of rubber attached to RSF surface had a negligible effect in the corrosion resistance of RSFRC.